2008
DOI: 10.1073/pnas.0800050105
|View full text |Cite
|
Sign up to set email alerts
|

Low-level viremia persists for at least 7 years in patients on suppressive antiretroviral therapy

Abstract: Residual viremia can be detected in most HIV-1-infected patients on antiretroviral therapy despite suppression of plasma RNA to <50 copies per ml, but the source and duration of this viremia is currently unknown. Therefore, we analyzed longitudinal plasma samples from 40 patients enrolled in the Abbott M97-720 trial at baseline (pretherapy) and weeks 60 to 384 by using an HIV-1 RNA assay with single-copy sensitivity. All patients were on therapy (lopinavir/ritonavir, stavudine, and lamivudine) with plasma HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
583
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 576 publications
(622 citation statements)
references
References 27 publications
28
583
6
Order By: Relevance
“…[7][8][9][10][11] Because residual HIV expression continues despite effective ART [12][13][14][15][16] and is required for viral rebound, HIV-infected cells should theoretically be targetable by a T cell therapeutic agent. Several mechanisms are thought to be responsible for the apparent failure of autologous cytotoxic T lymphocytes (CTLs) to clear reactivated cells in HIV-infected individuals: HIV evolution prior to ART quickly selects for CTL escape mutations; [17][18][19] HIV Nef mediates downregulation of major histocompatibility complex class I (MHC-I), 20,21 protecting HIV-infected cells from T cell receptor (TCR)-dependent CTL killing; and HIV-specific CTL responses may be limited by exhaustion 22,23 or peripheral immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Because residual HIV expression continues despite effective ART [12][13][14][15][16] and is required for viral rebound, HIV-infected cells should theoretically be targetable by a T cell therapeutic agent. Several mechanisms are thought to be responsible for the apparent failure of autologous cytotoxic T lymphocytes (CTLs) to clear reactivated cells in HIV-infected individuals: HIV evolution prior to ART quickly selects for CTL escape mutations; [17][18][19] HIV Nef mediates downregulation of major histocompatibility complex class I (MHC-I), 20,21 protecting HIV-infected cells from T cell receptor (TCR)-dependent CTL killing; and HIV-specific CTL responses may be limited by exhaustion 22,23 or peripheral immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Assays of infectious virus recovery from quiescent CD4 + T cells isolated from patients on ART have revealed the existence of a reservoir of latent, replication competent HIV-1 with a half-life of 44 mo (1)(2)(3)(4). In addition, low-level plasma viremia persists indefinitely on ART (5,6), and the level of virus in plasma rebounds following cessation of ART (7,8). New therapeutic approaches are required to eliminate both persistent low-level viremia and the latent proviral reservoir.…”
mentioning
confidence: 99%
“…Thus, the enhanced replication fitness of HIV A02 in combination with loss of contacts for RTV in the active site of PR A02 may well explain the compromised activity of RTV (EC 50 , Ͼ1 M) against HIV A02 in the antiviral assays. In the case of patients, a study based on the Abbott M97-720 trial showed that low-level viremia could persist at least for 7 years in patients on an LPV/RTV regimen, partially due to latent viral reservoirs (36). Based on our structural analysis, amino acid substitutions (both active site and non-active site) in PR A02 caused an altered binding orientation of RTV in the active site, resulting in a significant loss of contacts in the S2 and S2= binding pockets of PR A02 and, consequently, causing HIV-1 resistance to RTV.…”
Section: Discussionmentioning
confidence: 99%